Emanation of brain frontal midline and brain mental theta signals as the source to explore the neural substrates of melodic and rhythmic holy quran - Rani, Nur Syairah Ab (2021)
Frontal midline theta (FMT) and frontal mental theta, as recorded from electroencephalography (EEG) and magnetoencephalography (MEG) respectively, had been regarded as the neural substrates for the cognitive brain function that correlate with the positive effects of music and meditation-related complementary therapy. Similar positive effects are also linked with the listening and recitation of rhythmic, melodic Holy Quran. However, limited studies on brainwave, in particular alpha wave, had been previously reported in the setting of Quranic verse recitation, with no previous study exists in relation to theta brainwave to our best knowledge. In this study, we explored the potential involvement of the frontal midline theta (FMT) (EEG) and frontal-mental theta (MEG) signals as the neural substrates in mapping the cerebral representations of the melodic and rhythmic Quran recitation among Muslim and non-Muslim groups. Following an informed consent and psychological State Trait Anxiety Instrument (STAI) profile, a total of 30 healthy subjects were recruited into the study as dual faith groups (Muslim, n=15 and non-Muslim, n=15). Each subject underwent a simultaneous EEG-MEG recording whilst being exposed to a random, passive listening of different known styles of Quranic recitation of Ayatul Kursi verse (namely Murattal Asim, Murattal Susi, Tarannum Asli and Hadr) as well as non-Quranic rhythms (namely Arabic News, Arabic Poem, Harekrishna and Monochord). Raw EEG-MEG data were analysed using Brainstorm with MATLAB, based on 20 brain regions of interest (ROI) for cerebral localization which included ACCpre, ACCsub, MCC, PCC, AMYG, PFCventmed, SFG, FMG and SFGmedial. The STAI scores indicated no significance differences found among groups and gender, with one subject (Muslim group) with very high STAI score (and was excluded from subsequent analysis as an outlier). In resting state condition, the source estimation for FMT in EEG data showed both groups had similar activations at SFGmedial while frontal mental MEG data indicated that the Muslim group had activation at MCC compared to non-Muslim which had activation at ACC and PCC. In Quranic recitation styles (Muslims group), MCC involved in Murattal Asim style (moderate tempo), FMG, ACC, MCC in Murattal Susi (moderate tempo), PCC and MCC in Tarannum Asli (slow tempo) and PCC, MCC in Hadr (fast tempo). In contrast, for the non-Muslim group, Murattal Asim has activation at PCC, Murattal Susi in ACC and PCC, Tarannum Asli and Hadr has similar finding in PCC. For correlation analysis among brain ROI, EEG data showed all 20 ROIs in FMT with strong, positive correlations. For MEG data, Muslim group showed strong, positive correlations in selected ROIs for the different Quranic recitation styles, and likewise the case for non-Muslim group but with key differences for certain recitation styles and ROIs. In Muslim groups, AMYG, SFG, ACCsup, ACCsub were activated during Murattal Asim, Murattal Susi and Hadr styles while MCC and PCC involved in Tarannum Asli recitation (slow tempo). In non-Muslims group, ACCpre, ACCsup,SFG, PFCventmed, AMYG were found activated during Murattal Asim, Murattal Susi and Hadr while SFG and ACCpre involved in Tarannum Asli recitation (slow tempo). In comparison between group and within Quranic and non- Quranic stimuli, mix ANOVA on EEG data showed no significant difference between the groups and within stimuli while MEG data indicated a significant difference between group in right PCC, and in the interaction among stimuli and group in left AMYG. Overall, both Muslims and non-Muslims groups showed different neural representation in several brain areas. FMT (EEG) and frontal mental theta (MEG) signals represent the novel underlying neural substrates of the Quranic recitation in different styles which involved brain ROI for cognitive functions such as emotion, decision making, rewarding stimuli and planning. The source estimation of EEG showed a slight difference compared to MEG as sensitivity of EEG mainly at scalp surface while MEG can capture the potential signals from the deep brain areas.